Astrologia aplicada ao produto de moda feminina - Souza, Rubia Maliski de (2016)
Astrology is a millenarian approach popularized in anun usual and curious way through various means of communication, a subject still much questioned as to its reliability in relation to the stars x individual, but it becomes a constant target for the desenvovelment of fashion collections or anyother creation segment dueto the ramifications that it reaches. The subject of the present study is not considered a science, but a im stoin corporate astrology as a methodo faiding the formation of feminine publicidentity, based on the concept so fanaly tical psychology developed by the psychoanalyst Carl Gustav Jung, applied in a Acollection of fashion that presents characteristics of the personality of each sign, represented in groups of affinities, through the elements of nature.